Avaliação do programa agente comunitário de saúde (pacs) no município de Maracanaú/CE - Silva, Renato Santos da (2023)
This research proposes to evaluate the Community Health Agent Program (PACS), within the scope of the Family Health Strategy (ESF), in Maracanaú/CE. Its central objective is to evaluate the strategies and actions of Community Health Agents (ACS) and their impact on preventive health in the primary care network offered in the municipality, and more recently, in the context of the pandemic caused by COVID-19. With regard to methodological aspects, this study is characterized by the predominance of aspects of a qualitative nature, using techniques and a set of instruments, which allow the triangulation of data and their analysis through document analysis, participant observation, field diaries, interviews and questionnaires (CHIZZOTTI, 2014; GIL, 2007), from the perspective of a constructivist and experiential base assessment proposed by Guba and Lincoln (1989). As for the results, it is observed that there is a strong dispute over the conception of the meanings of Primary Health Care (PHC) that inevitably shaped the practices and attributions of the ACS in the context of formation and implementation of public policy. Furthermore, amid the liberalizing reforms of the State and the pandemic caused by COVID-19, there is the face of a public policy that, along with the SUS, has been suffering the effects of chronic underfunding and underfunding over time. Regarding the performance of the ACS, especially in the context of the pandemic and COVID-19, what emerged was the underutilization of this worker and of Primary Care as a whole, revealing the direction adopted by governments for serious cases and the disregard of the place of PHC as a preventive health irradiation center.